Liver fibrosis assessed via noninvasive liver fibrosis scores is associated with atherosclerotic cardiovascular disease in middle-aged and older patients with prediabetes - Huang, Ying; Yuan, Yuan; Wu, Huixian; Zhou, Zhiyuan; Li, Lianhong; Huang, Xiaolong; Xin, Letong; Li, Jingru; Zhang, Junhan; Liu, Caiping; Zhu, Qun (Frontiers in Endocrinology, 2026)
BackgroundMetabolic dysfunction-associated steatotic liver disease-related liver fibrosis is linked to an increased risk of atherosclerotic cardiovascular disease (ASCVD); however, its impact on patients with prediabetes remains unclear. The aim of our study was to investigate the associations between ASCVD and three noninvasive liver fibrosis scores, including the fibrosis-4 index (FIB-4), nonalcoholic fatty liver disease fibrosis score (NFS), and aspartate aminotransferase-to-platelet ratio index (APRI), in middle-aged and older patients with prediabetes.MethodsIn this cross-sectional study, a total of 7,409 patients with prediabetes aged 40 to 80 years were classified into two groups based on their ASCVD statuses. Logistic regression analysis was performed to explore the relationships between liver fibrosis scores and ASCVD. Restricted cubic spline (RCS) curves were employed to explore potential nonlinear relationships. The performances of the liver fibrosis scores were compared using receiver operating characteristic (ROC) curves.ResultsNoninvasive liver fibrosis scores, including FIB-4, NFS, and APRI values, were independently associated with an increased likelihood of having ASCVD in middle-aged and older patients with prediabetes. After adjusting for confounding factors, the patients in the high-risk FIB-4, NFS, and APRI groups had 1.5, 2.6, and 1.5 times the odds of ASCVD, respectively, compared with those in the low-risk groups, with odds ratios and 95% confidence intervals of 1.497 (1.089–2.055) for FIB-4 (P = 0.013), 2.632 (1.949–3.560) for NFS (P < 0.001), and 1.483 (1.092–2.002) for APRI (P = 0.011). RCS analysis revealed a nonlinear positive correlation between FIB-4 and ASCVD, whereas the relationships between NFS and ASCVD and between APRI and ASCVD were approximately linear. In the ROC curve analysis, both FIB-4 and NFS exhibited area under the curve values exceeding 0.7 in detecting individuals with ASCVD, whereas APRI was a relatively poor discriminator of ASCVD.ConclusionsLiver fibrosis assessed via noninvasive indices was significantly positively associated with an increased risk of ASCVD in middle-aged and older patients with prediabetes, thereby underscoring the value of liver fibrosis scores as reliable indicators for identifying the presence of ASCVD in individuals with prediabetes.